Defining global benchmarks in elective secondary bariatric surgery comprising conversional, revisional and reversal procedures. (28th May 2021) - Gero, D; Vannijvel, M; Okkema, S; Deleus, E; Lloyd, A; Lo Menzo, E; Tadros, G; Raguz, I; San Martin, A; Kraljević, M; Mantziari, S; Frey, S; et al.
Abstract: Objective: Management of poor response and of long-term complications after bariatric surgery (BS) is complex and under-investigated. Indications and types of reoperations vary widely and postoperative complication rates are higher compared to primary BS. Benchmarking uses best performance in a given field as reference point for improvement. Our aim was to define ''best possible'' outcomes for elective secondary BS. Methods: The establishment of benchmarks in secondary BS followed a standardized methodology, based on recommendations of a Delphi consensus panel of experts. This multicenter study analyzed patients undergoing elective secondary BS in 18 high-volume centers on 4 continents from 06/2013 to 05/2019. Twenty-one outcome benchmarks were established in low-risk patients, defined as the 75th percentile of the median outcome values of the centers. Benchmark cases had no: previous laparotomy, diabetes, sleep apnea, cardiopathy, renal insufficiency, inflammatory bowel disease, immunosuppression, history of thromboembolic events, BMI>50kg/m2 or age>65 years. Descriptive statistics, multivariate logistic regression and data visualization were performed using the R software. Results: Out of 44'884 elective bariatric procedures performed in the participating centers, 5'328 secondary BS cases were identified. The benchmark cohort included 3143 cases, mainly females (85%), aged 43.8±10 years, 8.4±5.3 years after primary BS, with a body mass index 35.2±7kg/m2. Main indications were insufficient weight loss (43%) and gastro-esophageal reflux disease/dysphagia (25%). 90-days postoperatively, 14.57% of benchmark patients presented ≥1 complication, mortality was 0.06% (n = 2). Significantly higher morbidity was observed in non-benchmark cases (OR 1.36) and after conversional or revisional procedures with gastrointestinal suture/stapling (OR 1.7). Benchmark cutoffs at 90-days postoperatively were ≤5.8% re-intervention and ≤8.8% re-operation rate. At 2-years (IQR 1-3) 15.6% of benchmark patients required a reoperation. Conclusion: Secondary BS is safe, although postoperative morbidity exceeds the established benchmarks for primary BS. The excess morbidity is due to an increased risk of gastrointestinal leakage and higher need for intensive care. The considerable rate of tertiary BS warrants expertise and future research to optimize the management of non-success after BS.